Distinção, corpo de classe e estilo de vida: “as situações que a gente passa, dentro das novelas têm” - Marques, Camila da Silva (2018)
This thesis is a comparative study of soap opera reception with 8 upper middle, middle and popular classes women (middle low and low) residing in Santa Maria, Rio Grande do Sul. The social bias of the present research is the social class, here understood as a key mediation to comprehend the tangles between media and sociocultural contexts. The objective is to comprehend the similarities and differences in the interpretation of class and distinctive processes presented in the narrative of the soap opera A Regra do Jogo (2015/2016) - which aired at 9 p.m., considered the main hour for soap operas, at Rede Globo, a Brazilian TV channel – performed by women from different social classes. Seeking to handle with the social usages of the soap opera, mainly to its role of perception and conformation of the life style experienced in the daily life have been observed. In order to articulate a theory of social/cultural matrix and a communicative matrix, two main theoretical-analytical axes have been worked: the Bourdieu sociology (habitus, distinction, life style, capitals, body class) and the Latin-American reception studies (Map of the Communicative Mediations of the Culture of Martín-Barbero ([1998] 2003). Through a critical appropriation of the so-called nocturnal map (RONSINI, 2011, 2016), the analytical stage is divided by two scopes. To contextualize the soap opera that composes the corpus of this work, the representations of class and distinctive processes presented in A Regra do Jogo have been examined through the technicality mediation. For the reception sphere, the uses and (re)appropriation of class presented in the representations of class produced by soap operas have been comprehended into: 1) sociality, to capture the ways of being and the life style of the receptors and 2) rituality, seeking to embrace the ways of seeing and interpreting the soap opera. The epistemology of the investigation follows the Critical Studies of Reception (RONSINI, 2011), through a prolonged fieldwork with the informants. The results show that the feminine representations of A Regra do Jogo – connected to the traditional notions of motherhood and conjugal love, of women that work but does not leave the administration of the house, in addition taking body and beauty care – are interpreted by receptors of all social classes being the ones who best represent the Brazilian women. However, there are some divergences in these interpretations: while the receptors by upper and middle classes believe the poor characters are well represented by the materiality of a popular life style in the language, appearance, little clothing and gestures; the receptors of the popular classes criticize strongly the vulgar clothing, the grammatical mistakes, the promiscuous behavior and the absence of insertion of those characters in working and study environments. These data points that different interpretation of the class and gender representations produced at A Regra do Jogo engage in the processes of identification and disidentification of the informants with life style that demarcate the distinctions among the classes. All the informants disidentify themselves with the life style of the characters who are considered “vulgar”, “cheesy”, “showy” and “flamboyant”: the receptors of upper and middle classes, justly because they believe these characteristics reflect the reality of popular classes outside the TV, they do not represent them, while the popular class women do not recognize themselves in those representations and that is why they reject them. All of them identify and/or Project themselves in the feminine representations that are “elegant”, “fancy”, “workers”, “fighters”, “good mothers” and “beautiful”: mostly the characters who do not belong to the popular area.